Social Integration, Self-control, and Conformity - Welch, Michael R. (Journal of quantitative criminology, 2008)
Evidence relevant to claims of self-control theory concerning the connection between social integration and crime/deviance is offered. Using data from a survey of the population of a southwestern city that permit measurement of two types of social integration, including socially supportive networks, we (1) investigate the association between self-control and social integration, and (2) attempt to ascertain if social integration is associated with misbehavior independently of self-control. Results suggest that self-control is a persistent predictor of misconduct that operates independently of social integration. Although interpersonal social integration appears to stand alone in its association with deviance, community integration shows no relationship with self-control or misbehavior.